ANALYSIS OF THE EFFECTIVENESS AND CONTRIBUTION OF TAX REVENUE AGAINST THE ORIGINAL PARKING AREA (PAD) SURAKARTA CITY YEAR 2012-2016 - Sari, Mariani (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this research is to analyze the effectiveness of tax revenues and analyze the contributionof income tax Revenue against the Original Parking area (PAD) Surakarta city in 2012 â 2016. Researchusing the method of the case study, the type of data used quantitative data, the source data used aresecondary data. The technique of data used is descriptive analysis. The research results obtainedconclusion: the effectiveness of tax revenue parking in Surakarta from the year 2012 â 2016 that isincluded in the criteria is very effective. It means in the year 2012 â 2016 realization of tax revenueexceeds the target parking lot. The contribution of Tax Revenue against parking Areas of Surakarta cityyear 2012 â 2016 i.e. have a fluctuating contribution. The highest contribution levels occurred in the year2016 with the percentage of 0.81%, while the lowest contribution occurring in 2013 with a percentage of0.68%. Tax contributions against tax Parking areas in Surakarta from the year 2012 â 2016 on average are0.75%. If based on criteria or indicators of research contributions, then his judgment entry category isvery less.Keywords:[ Parking; Tax Effectiveness; Contribution; PAD]